When normative framing saves Mr. Nature: Role of consumer efficacy in proenvironmental adoption - Do, Khoa T.; Wang, Chen‐Ya; Guchait, Priyanko (Psychology & marketing, 2021)
This study examines the proenvironmental persuasion of the so‐called normative framing that incorporates normative influence (i.e., social norms) into message framing (i.e., loss vs. gain). Across three green contexts (i.e., towel reuse, paperless adoption, and ugly food consumption), this study shows that normative gain is consistently more effective than both normative loss and pure normative influence in promoting proenvironmental act, which is particularly motivated by positively framed information under the prospect‐theoretic reasoning. This superior effect of normative gain is explained by the psychological sequence from collective efficacy to self‐efficacy as the serial underlying mechanism. This study further unveils the boundary condition of anthropomorphism in amplifying this superiority (i.e., Mr. Nature, happy earth face) and reveals that the advantageous effect of normative gain is stronger among those low in interdependent self‐construal. Our findings might provide helpful and relevant guidelines for businesses to operate sustainably by shifting their customers' behaviors to be greener.